Carakā-buleṭa-byālaṭa - Krttibāsa Ojhā, 1930- (Iṇḍiẏāna Renesām Pābalikeśanas, 1983)
Life and philosophy of Pramoda Dāśagupta, former chairman, West Bengal State Committee of the Communist Party of India (Marxist)